Nanostructured, Highly Anisotropic, and Mechanically Robust Polymer Electrolyte Membranes via Holographic Polymerization. Issue 1 (9th November 2017) - Smith, Derrick M.; Pan, Qiwei; Cheng, Shan; Wang, Wenda; Bunning, Timothy J.; Li, Christopher Y.
Abstract: Solid polymer electrolytes have shown to be a promising solution to suppressing dendrite growth for safer and higher performance lithium batteries. This article reports the fabrication and characterization of a series of nanostructured polymer electrolyte membranes (PEMs) comprised of poly(ethylene glycol)/bis(trifluoromethane)sulfonimide lithium electrolyte and acrylate–thiol‐ene crosslinked resin using a holographic polymerization (HP). Nanoscale long‐range order is observed and this unique structure imposes intriguing mechanical and ion‐conducting properties of the PEMs. The modulus of the holographically polymerized PEMs can be tuned to vary from 150 to 1300 MPa while room temperature conductivities of ≈2 × 10 −5 S cm −1 and 90 °C conductivity of ≈5 × 10 −4 S cm −1 are achieved. The HP nanostructure is also capable of directing ion transport either parallel or perpendicular to the membrane surface; an unprecedented ionic conductivity anisotropy as high as 3 × 10 5 is achieved. It is anticipated that these PEMs may be excellent candidates for lithium battery applications. Abstract : Nanostructured solid polymer electrolytes are fabricated. The membranes show tunable mechanical properties from MPa to Gpa range. The membranes show an ionic conductivity anisotropy of ≈30 000.